The cell as a gel: materials for a conceptual discussion - Bagatolli, Luis A. (2016)
Recent results from our laboratory support the view that the intracellular milieu cannot be treated as a homogeneous dilute system and, more importantly, reveal for the first time a dynamical coupling between intracellular water and an active metabolic process involving fluctuations in ATP concentration. These results are difficult to understand in light of the premises that currently underpin the description of the function of cellular systems, e.g. van’t Hoff’s ideal solution theory, diffusion and mass action kinetics. Particularly, they emphasize the need to incorporate features of the cell interior that have been largely overlooked in the dominant model of the cell, such as crowding and limited availability of free water. This article discusses this problem by reconsidering an alternate view, called the association-induction hypothesis, which emphasizes the relevance of emergent properties of the cell cytosol during cellular function. This hypothesis provides a very reasonable theoretical framework to explain recently reported observations about the dynamical coupling of mechanochemical (i.e. viscoelastic) properties of the cell cytoplasm and cellular chemical transformations (metabolism).